Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO267/2, Pacific Ocean - Dilip Adhikari; Annette Scheider; Daniela Voß; Stefan Kinne (PANGAEA, 2023)
The multibeam echo sounder (MBES) data was collected from the 03.02.2019 (09:44 UTC) to the 13.02.2019 (16:19 UTC) with the Kongsberg EM122 on RV SONNE during the transit from Suva (Fiji) to Manzanillo (Mexico) in the Pacific Ocean. The deep-water MBES EM122 operates with an acoustic frequency of 12 kHz and a beam opening angle of 0.5° x 1°. The raw and unprocessed bathymetric and backscatter data is stored in Kongsberg format (*.all), each containing up to 60 min of data. The therein included time, motion and position data (WGS84, geographic) was measured by the Kongsberg Seapath system on board. During the acquisition the echo sounder was monitored as well as settings and filter adjusted according to the environment. The transit speed was up to 13 knots. The swath opening angle was set to 70° resulting in a swath width of about 15 km in 3,000 m water depth. Further, high density and dual swath mode were used resulting in 2 x 432 beams per ping. As the data was collected during transit, no specific surveys were performed. No sound velocity profiles (SVPs) were measured during the cruise. In the beginning of data acquisition, an SVP from a previous cruise was used. On the 04.02.2019, a synthetic SVP extracted from he World Ocean Atlas 2009 from NOAA (Levitus, 2013) using the software "Sound Speed Manager" (developed by the UNH Center for Coastal and Ocean Mapping and NOAA Coast Survey Development Laboratory (CSDL)) was applied in the MBES acquisition software SIS. The SVP data is not part of this submission but can be extracted from the *.all files.